2017
DOI: 10.1038/nsmb.3362
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of dual Ca2+/pH regulation of the endolysosomal TRPML1 channel

Abstract: Organellar ion channels are essential for cell physiology. Their activities are often regulated by Ca2+ and H+, which are concentrated in many organelles. Here we report a novel structural element critical for Ca2+/pH dual regulation of TRPML1, a Ca2+ release channel crucial for endolysosomal functions. TRPML1 mutations cause mucolipidosis type IV (MLIV), a severe lysosomal storage disorder characterized by neurodegeneration, mental retardation and blindness. We obtained high-resolution crystal structures of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 63 publications
(90 reference statements)
7
115
0
Order By: Relevance
“…Our cryo-EM structure of the econazole-bound full-length TRPV5 channel exhibits a domain-swapped architecture, which is a hallmark of all currently determined TRP channels at atomic resolution 1118 and was recently confirmed to be present in TRPV6 (refs. 19,20 ).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Our cryo-EM structure of the econazole-bound full-length TRPV5 channel exhibits a domain-swapped architecture, which is a hallmark of all currently determined TRP channels at atomic resolution 1118 and was recently confirmed to be present in TRPV6 (refs. 19,20 ).…”
Section: Discussionmentioning
confidence: 56%
“…All recently determined cryo-EM structures of TRP channels have revealed a domain-swapped architecture that is shared by many voltage-gated ion channels 1118 . As expected, the full-length TRPV5 structure is similar to other TRPV subfamily structures 1113 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). The 200-residue, luminal-facing linker domain between S1 and S2 can self-assemble into a tetramer and its crystal structure 22 fits readily into our EM-density map, facilitating our model building. Asn230 of the luminal linker domain is glycosylated with visible density for the covalently linked N-acetylglucosamine moiety of the sugar (Fig.…”
Section: Main Textmentioning
confidence: 94%
“…The enrichment of Ca 2+ ions can effectively limit the access of monovalent cations to the filter and, thereby, reduce the permeation of monovalent ions. Indeed, it has been shown that neutralizing the acidic residues on the luminal pore loop weakens the Ca 2+ blockage 22 .…”
Section: Main Textmentioning
confidence: 99%